Concepções prévias de professores e formação continuada em modelagem matemática - Silva, Marcio Virginio da (2017)
Mathematical Modeling, as a tendency of Mathematics Education, is not yet present in the scope of Basic Education. One of the factors that can contribute to overcoming this situation is the training of teachers. Teachers have their own conceptions about teaching, learning, mathematics and methodology in general. Considering this condition, a relevant research topic is the study of these conceptions, in a context of continuous formation. From this perspective, we were able to establish an interrogation, under a phenomenological view of research: In what ways do the prior conceptions of teachers operate in their continued formation in Mathematical Modeling? This question asks to be clarified and requests its own procedures, such as the understanding of the region of inquiry that we are in - teacher training in Mathematical Modeling - the definition of the type of research that we need to carry out - the qualitative one according to a phenomenological research position - The selection of instruments for the collection of significant material, the explicitation of aspects of the proposal for Continuing Education in Mathematical Modeling which has developed in different education centers in the state of Paraná and the ways in which we undertake analyzes and interpretations. The present research was developed within the group of Continuing Education in Mathematical Modeling established in the city of Tupãssi - Paraná, which counts with the participation of five professors in addition to the teacher who assumes the role of trainer. The material that was significant to the research was collected during 12 meetings of this group through audio recordings between the period of April 13, 2016 and September 21, 2016. For organization and analysis of the data we used Atlas software. We arrive to allow us to affirm that even teachers still finding themselves guided by the exercise paradigm present in their conceptions openness to pedagogical innovations such as Mathematical Modeling and in this way show us about the importance in pondering the ways in which the previous conceptions of teachers operate in Formation Continued in Mathematical Modeling. Be they as obstacles, potentialities, or other modes, in order to contribute to the elaboration of a proposal of Training in Mathematical Modeling that, contemplating these aspects, will favor the adoption of the Modeling by the teachers thus providing for the dissemination of the Modeling as a trend in Mathematics education.